A computer model designed to evaluate the firefighting effectiveness of solid jet produced by water nozzle - Gałaj, Jerzy; Drzymała, Tomasz; Šukys, Ritoldas; Tofiło, Piotr (Journal of Civil Engineering and Management, 2018)
The paper begins with a brief introduction and review of international research in the area of water jet streams and their effectiveness in firefighting. Then a general concept of a new numerical model for firefighting process using solid jet produced by water nozzle is presented. The provided description of the model includes main assumptions for extinguishing process and a set of relationships representing a mathematical model. The paper also includes block diagrams of the main program algorithms and procedures designed to determine the value of the surface and sprinkling intensity depending on the input data like nozzle dimensions, position etc. Input parameters which are necessary for the calculation are discussed, together with a general concept of the users input and output interfaces and simulation tests that can be performed using the developed model. Some selected simulation tests in tabular and graphical forms are included. Summary and general conclusions can be found at the end.